Teacher's passion and how it affects student's learning passion in Sabah / Nurdalilah Yusaida Saiman, Nur Ain Amad and Jennifah Nordin - Saiman, Nurdalilah Yusaida; Amad, Nur Ain; Nordin, Jennifah (2021)
Passion is a very prominent element in performing the job and it is referred to as someone's desire, motivation, and liking, seeing the importance of doing a job, engagement, and willingness to contribute time and energy to it (Carbonneau et al., 2008). This study focuses on two main variables that are teacher's passion and student's learning passion. Teachers' passion is defined hers those who love educating students and can inspire and stimulate the learning lives of their students (Liston & Garrison, 2004). While student's passion of learning can be defined as time devoted, commitment, persistence, academic commitment, intense interest, and motivation in learning (Ruiz Al-Fonso et al., 2018). It would be interesting to note that if a student persists on a task, spends a lot of time, and is committed to it, it could also benefit his/her academic performance (Ruis Al-Fonso et al., 2018). Teachers' passion seems crucial since it will have a strong impact on students learning experience and students' learning outcomes. Working as a teacher is a noble job since a teacher is a person that will work hard to educate and teach the students. Ideally, besides teaching, teachers are required to perform many roles such as doing clerical works, being a curriculum advisor, coaches in the sport, handling student records, and disciplining students. Teachers have to undertake redundant works which have become more burdening (The Star, 2018). Teachers are stress and no longer able to deliver quality teaching and it has a significant impact on students' learning performances (Ismail et al., 2012, as cited in Noor et al., 2019). Pandemic Covid-19 hit also impacted teachers' passion and students' passion since learning needs to be conducted online. The coronavirus outbreak had affected the educational system and students' learning experience. One of the challenges is a physical limitation where students and teachers were located at a different place which limits real-time interaction, creates difficulty, and develops frustration in doing their group task (Thompson & McDowell, 2019). Students miss their face-to-face classes and synchronised meetings with classmates and teachers. It means the pandemic is a challenge for students and teachers in developing effective learning sessions.